Assessment of Serum Vitamin D, Serum Calcium and Bone Mineral Density in Juvenile Idiopathic Arthritis Patients of Bangladesh (Bangladesh Journal of Nuclear Medicine, 2026)
Objective: To assess the serum concentrations of vitamin D and calcium and bone mineral density (BMD) in patients with juvenile idiopathic arthritis (JIA) and to compare them with those of healthy children. Patients & Methods: A total of 75 JIA children were evaluated and compared to healthy individuals matched for age and sex in this cross-sectional case-control study. Laboratory evaluations included serum calcium and 25-hydroxyvitamin D. The normal range of serum calcium was 9-11 mg/dl; vitamin D was classified as normal (>32 ng/ml), insufficient (20-32 ng/ml), and deficient (